Traumatic spinal cord injury caused by a dagger in the spine: A case report. Issue 3 (25th March 2022) - Zhou, Hong‐Su; Pi, Yu; Wang, Chong; Ao, Jun; Sun, Lv; Yuan, Hao
Abstract: Acute traumatic spinal cord injury (SCI) combined with foreign matter retention is rare in the clinic, which causes less literature reported, browsed, and analyzed. A 36‐year‐old male was rushed to our institution due to an attack on the back. His superficial sensation below the nipple had disappeared (mainly in the left breast), the proprioception of both lower limbs was obviously decreased, and the muscle strength of the left lower limb was level 0 and that of the right lower limb was level 3. Computed tomography of the thoracic vertebrae showed that the dagger had completely pierced into the T9 vertebral body and the spinal canal. Prehospital transport: the spinal cord may be injured again due to the movement of the remaining foreign matter and the posture of the patients while they are being transported. Pathophysiology: the incidence of incomplete SCI is higher than that of other types of SCI. Imaging examination: magnetic resonance imaging might cause unexpected secondary injuries. Treatments: surgical intervention including removal of foreign matter and decompression is an essential and important measure for recovery of neurological function. Patients could benefit from administration of methylprednisolone. Abstract : Although cases of acute spinal cord injury (SCI) combined with foreign body retention are relatively rare and are found less frequently, the possibility of extreme events that could lead to personal or even family breakdown cannot be ignored. In this study, we aimed to review and discuss prehospital transport, pathophysiology, imaging examination, and treatments for such patients sufferring from an attack of the back, causing acute SCI combined with foreign matter retention. This study shows that early surgical intervention, combined with other supportive care after surgery, and maintaining stable vital signs, prehospital transport, pathophysiology, and radiology for such patients are important to avoid secondary spinal cord injury.